2021
DOI: 10.1080/09638288.2021.1988736
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sustaining work with chronic spinal cord injury: a scoping review

Abstract: Work participation remains challenging for people with spinal cord injury (SCI), as reflected in lower employment rates compared to the general population. To promote work participation for people with SCI, practitioners and policymakers need a better understanding of the factors associated with sustaining work in the long term. This study aimed to identify such factors. Materials and methods: Scoping review synthesizing quantitative and qualitative research published between 2000 and 2021. The databases searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…The aspects raised by the employers interviewed in connection with sustainable employment largely coincide with the findings of existing international studies that look at the period of vocational rehabilitation or working with ABI or SCI in general (21,22). In addition, these studies also found that many aspects that our study identified as important for a sustainable work ability are initiated and established during the vocational reintegration phase.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The aspects raised by the employers interviewed in connection with sustainable employment largely coincide with the findings of existing international studies that look at the period of vocational rehabilitation or working with ABI or SCI in general (21,22). In addition, these studies also found that many aspects that our study identified as important for a sustainable work ability are initiated and established during the vocational reintegration phase.…”
Section: Discussionsupporting
confidence: 80%
“…For people with SCI, the importance of self and health management and adaptations in the work environment, as well as support from work colleagues, is emphasized. Barriers to sustainable work ability relate to difficulties in work organization and social discrimination (21). Specific, though not surprising, the interviewees focused strongly on performance as a critical factor to sustained employment and the challenges associated with discrepancies in performance expectations between employers and employees, what was also pointed out by Gilbride et al (26).…”
Section: Discussionmentioning
confidence: 72%
“…They also overlap with key determinants of a successful RTW (31)(32)(33)(34)(35)(36)(37), indicating that some of the factors that are important for RTW remain significant in the long run. For example, being understood and supported by others at work and in private life is important for both RTW and sustaining employment as found by previous research (6,7). However, as shown in our study and previously reported, support at the workplace tends to diminish over time 1 .…”
Section: Discussionsupporting
confidence: 78%
“…Sustaining work reflects a major challenge for people with a disability, as evidenced by premature withdrawals from the labor market and a significantly decreasing employment rate over the life course (1)(2)(3). While return to work (RTW) is a primary goal of vocational integration services, many affected persons face problems in maintaining their jobs after initial RTW and tend to drop out from the labor market in the long run (3)(4)(5)(6)(7). By contrast to the predictors of a successful RTW, factors that determine labor market dropouts and a sustainable employment over time are hardly investigated in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation